Effects of sickness on weight gain and radiant energy loss in recently received feeder cattle - M.F. Spire; J.M. Sargeant; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2000)
Sickness from undifferentiated respiratory disease in recently received feeder cattle reduced weight gain and altered radiant energy loss. Over a 35-day receiving period, weight gains were reduced 26.3% if an animal was diagnosed as sick once and 48.1% if diagnosed sick more than once. Thermal profiles obtained 10 or more days following clinical illness were cooler than profiles of animals never diagnosed as being sick. Our data suggest that respiratory disease alters metabolic activity as evidenced by reduced weight gain and a detectable decrease in radiant energy loss from the body surface.
Keywords: Cattlemen' s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Infrared thermography; Sickness; Feedlot performance